On the lumped damage modelling of reinforced concrete beams and arches - Thalyson Issac de Jesus Brito; Danilo Menezes Santos; Fabio Augusto Silva Santos; Rafael Nunes da Cunha; David Leonardo Nascimento de Figueiredo Amorim (Fracture and Structural Integrity)
The analysis of reinforced concrete structures can be performed by means of experiments or numerical studies. The first way is usually quite expensive, so the second one sometimes is a good option to understand the physical behaviour of actual structures. Lumped damage mechanics appears as one of the latest nonlinear theories and presents itself as an interesting alternative to analyse the mechanical behaviour of reinforced concrete structures. The lumped damage mechanic applies concepts of the classic fracture and damage mechanics in plastic hinges for nonlinear analysis of reinforced concrete structures. Therefore, this paper deals with a novel physical definition of the correction factor ? for cracking evolution that ensures the presented lumped damage model depicts accuracy when it is compared to experimental observations of reinforced concrete beams and arches. Based on such experiments, the numerical analysis showed that ? value has upper and lower thresholds, depending on the physical and geometric properties of the reinforced concrete element. Notwithstanding, for ? values inside of the proposed interval, there is a best value of ?.